Parenting Style for Children with Special Needs - Benu, Juliana Marlin Y; Nge, Yolenta Chinora Chindi; Ratu, Feronika (Universitas Nusa Cendana, 2023)
Children with special needs are children who experience abnormalities (physical, mental-intellectual, social, and emotional) and need special attention. In carrying out their daily activities, children with special needs need assistance from their families, especially their parents. The parenting style of parents who have children with special needs is different from children in general. Parents need knowledge about proper parenting for children with special needs. The purpose of this study was to describe the parenting style of children with special needs at SLB Negeri Tenda Ruteng. This research is a type of qualitative research with descriptive methods. Sampling in this study was purposive sampling. The result of this study shows that parenting style is related to the following four things, namely parenting, aprreciation, communication between parents and children, and disciplining.